THE FORMING OF SPONTANEOUS SOCIAL INTERACTION PLACE IN KAMPUNG TRANSITION AREA, PRAWIROTAMAN, INDONESIA - Tika Ainunnisa Fitria; Mohd Hisyam Rasidi; Ismail Said , (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Prawirotaman is a traditional urban settlement in Yogyakarta. In the 19th Century, it was a Sultan’s soldier family settlement. Nowadays, it is a tourism destination known as a tourism village that serves tourism facilities, such as homestay, cafe, pub, and other tourism businesses. This transformation affects the locals in using the transition area as a place for social interaction activities. The transformation of Prawirotaman is a key to observe how the residents form the spontaneous social interaction place through the tendency of transition area use. While this paper emphasizes primarily the identification relating to the variables 1) boundary element, 2) spontaneous interaction, and 3) territorial depth, this research proposes a comprehensive conclusion for reflecting the forming of transition area at the kampung in accommodating the social interaction in term of the kampung settlement transformation. Thus, the fundamental question of this research is how the spontaneous interaction places occurred, the factors and typology. The primary data collection was collected through field observation and interviews to find the sample of potential interaction space. The method of data collection in this research uses snapshot observation and ArcGIS for redrawing the satellite map and spatial analysis. The finding results there are general typologies that describe the forming of spontaneous interaction places in Prawirotaman, namely 1) Filtered visual transparency, 2) Full visual transparency, 3) Closed visual transparency, 4) In the transition area.